An alternative approach to measure alpha-particle-induced SEU cross-section for flip-chip packaged SRAM devices: High energy alpha backside irradiation. (February 2017) - Khan, Saqib Ali; Lim, Chulseung; Bak, Geunyong; Baeg, Sanghyeon; Lee, Soonyoung
Abstract: To evaluate a device sensitivity against alpha particles, traditional Single Event Effect (SEE) tests are conducted using isotope source, which emits particles just above 5 MeV. Relentless downscaling and higher packing density have driven the demand of developing increasingly complex packaging: smaller, thinner, having enormous input/output pins count per chip. Flip-chip bonded devices meet all these demands, but their testing against alpha particles is a big challenge. The range of alpha ions, emitted by the isotope sources, is very short, which precludes their penetration till active circuit – from either side of the chip. This paper presents an evidence that high energy alpha irradiation can potentially be used to measure and correlate alpha SEE cross-section for such devices. The proposed method uses high energy alpha particles, directed from the backside of die, to mimic low energy ( 5 MeV) at the sensitive volume (SV). The incident particles penetrate the entire silicon substrate and deposit charge in the SV to induce upsets. The energy and LET of an ion at the SV, having traversed the entire substrate, is determined using TRIM. SEE experiments are performed on 14 nm FinFET SRAM devices, assembled in flip-chip and wire-bonded structures, respectively, for backside and traditional top-side testing. High energy alpha irradiations were simulated using CRÈME-MC – a Geant4 based Monte Carlo transport code. Tests and simulation results, for traditional and proposed methods, are presented for correlation. Highlights: New approach to measure alpha particle induced Single Event Upset Cross-section for flip-chip packaged Devices High energy alpha particles irradiation is performed from backside to die to deposit charge in the active circuit of device High energy alpha particle irradiation from backside of die mimics low energy alpha emitted from radioactive impurities The cross-section measured using new approach is consistent with that of measured using conventional method This method allows flip-chip bonded devices to be tested without having to etch away part of package and chip from backside